On the Origin of “Laozi Converting the Barbarians”: A Historical Background Analysis - Si, Jiamin; Han, Jishao 1980-; Zhang, Yuan (2023)
This article examines the historical background of “Laozi huahu 老子化胡” (Laozi converting the barbarians) and investigates its generation mode and constituent elements. It also discusses and reflects on issues such as the origin of “huahu” and Laozi’s deification. The origin of “Laozi huahu” has little relationship to issues such as the divine system in the Han dynasty and Laozi’s deification. Its elements are rooted in Chinese secular ideological resources. The story of “heroes moving across borders” during the Spring and Autumn and Warring States periods, along with the notion of Laozi as the universal teacher for disciples of various schools, gave birth to the saying. An analysis of the historical background suggests that the origin of “huahu” had likely gone through a long evolutionary process, including an undocumented period where it was transmitted orally as a legend.
Keywords: Laozi’s deification; Ethnic relations; Origin; “Laozi Huahu (converting the barbarians)”